Letter - Sutherland, Mary E.
1938-12-23 038-0113-001 SPANISH RELIEF COMMITTEE under the auspices of the STANDING JOINT COMMITTEE OF INDUSTRIAL WOMEN'S ORGANISATIONS Chairman: Mrs. H.T. LEIGHTON Secretary: MARY E. SUTHERLAND, J.P. Victoria 9434 TRANSPORT HOUSE, (South Block), SMITH SQUARE, LONDON, S.W.1. 23rd December, 1938. Mr. H.V. Tewson, Trades Union Congress, Transport House, Smith Square, S.W.1. Dear Mr. Tewson, I attach copy of a letter which I have had from Mrs. Rickard of Croydon, who has regularly sent the money from the Women's Section through the International Solidarity Fund for the adoption of one child. Mrs. Rickard has had your receipt for the last sum she sent which paid up to December 26th. Perhaps you will take this matter up with the Basque Children's Committee. Yours sincerely, Mary E. Sutherland Secretary. Enclosure. 292/946/38/113(I)